2022
DOI: 10.1038/s41598-022-23572-4
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic restoration of high sensitivity vision with bReaChES, a red-shifted channelrhodopsin

Abstract: The common final pathway to blindness in many forms of retinal degeneration is the death of the light-sensitive primary retinal neurons. However, the normally light-insensitive second- and third-order neurons persist optogenetic gene therapy aims to restore sight by rendering such neurons light-sensitive. Here, we investigate whether bReaChES, a newly described high sensitivity Type I opsin with peak sensitivity to long-wavelength visible light, can restore vision in a murine model of severe early-onset retina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
2
1
Order By: Relevance
“…4e). The estimated photon flux density is an order of magnitude lower than recently reported results at the lowest intensity to date, i.e., 0.04 µW/mm 2 (~ 1.03 × 10 11 photons mm −2 s −1 at 505 nm from LED) with ex3mV1Co, and 2-3 orders of magnitude lower than reported experiments with other opsins [15][16][17][18][19] . It is reported that sunlight intensity on earth ranges from 440 lx (3.5 µW/mm 2 ) to 93,500 lx (0.75 mW/mm 2 ) in open playground 48,49 .…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…4e). The estimated photon flux density is an order of magnitude lower than recently reported results at the lowest intensity to date, i.e., 0.04 µW/mm 2 (~ 1.03 × 10 11 photons mm −2 s −1 at 505 nm from LED) with ex3mV1Co, and 2-3 orders of magnitude lower than reported experiments with other opsins [15][16][17][18][19] . It is reported that sunlight intensity on earth ranges from 440 lx (3.5 µW/mm 2 ) to 93,500 lx (0.75 mW/mm 2 ) in open playground 48,49 .…”
Section: Discussioncontrasting
confidence: 65%
“…The retina has higher irradiance safety thresholds for red light 18 , 19 . Therefore, intense efforts have been made to discover new opsins exhibiting red-shifted activation spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Recent introductions include bReaChES, Chrimson variants, and ChroME2.0 opsins [ 25 , 44 , 52 , 58 ]. However, these channels still suffer from a wide activation spectrum and/or slow inactivation kinetics [ 48 , 52 , 53 ], limiting their applicability for cardiac research. Taken together, while these red-shifted ChRs do benefit from the deeper penetration of red light in cardiac tissue, combinations with proteins and compound stimulated by blue light and wavelengths above are still not possible.…”
Section: Optogenetic Actuatorsmentioning
confidence: 99%